How Burge avoids externalist equivocations (Diametros, 2008)
According to semantic externalism the meaning of many of our expressions is determined by our physical surroundings. A consequence of this is the impossibility to evaluate a priori the formal correctness of arguments. The article presents four ways of dealing with this problem: postulating a priori dependence on memory, analyzing the behavior of memory in deductive processes, postulating conscious and intentional dependence on memory in reasoning, and postulating the introduction of another premise into reasoning processes. The conclusion is that the first three solutions have undesirable epistemological and semantic consequences, and must therefore be rejected. The fourth solution seems the most promising and defensible.